Potensi Pengembangan Komposit Berpenguat Serat Kulit Gaharu Sebagai Material Pengganti Fiberglass Pada Pembuatan Dashboard - Masdani Masdani; Yuli Dharta (Manutech : Jurnal Teknologi Manufaktur, 2018)
The development of industrial in the utilization of composites as a substitute of metal materials that are used is fiberglass. However, fiberglass is considered not environmentally friendly because difficult to decipher. The technology advances, it is now widely used from composite materials with natural fibers.This research was conducted to obtain data about mechanical ability in the tensile strength, impact strength and physical form of Gaharu skin fibers using polyester matrix BQTN 157 with volume fraction variations made by hand lay-up method. This research is expected to be useful in automotive, manufacturing industry and household appliances are environmentally friendly. The maximum value of tensile strength is 34.574 MPa in 45% fiber volume fraction. However, there is a decrease in the tensile strength value in the 50% fiber volume fraction, which is 22,635 MPa, this is due to the large amount of fiber content so that the matrix spread to the fiber is uneven. The maximum impact strength value is 62.76 kJ / m2 at 50% fiber volume percentage. Based on the results of testing the comparison of the fiber and matrix volume fractions greatly affect the tensile strength and impact. The results show tensile and impact tests have met the plastic standards used car dashboards.